2020
DOI: 10.2147/cmar.s263525
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictive Factors and Long-Term Outcomes of Early Gastric Carcinomas in Patients with Non-Curative Resection by Endoscopic Submucosal Dissection</p>

Abstract: Non-curative resection (NCR) remains problematic in some cases of early gastric carcinomas (EGCs) treated by endoscopic submucosal dissection (ESD). The aim of this study was to identify predictors of NCR, especially of eCura C1 and eCura C2 resections, before ESD and study long-term outcomes of EGC patients with NCR. Patients and Methods: A retrospective review of medical records was conducted over an 8-year period for EGCs undergoing ESD. Clinicopathologic and endoscopic characteristics and patients' surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…In the context of ecological factors, age and gender have been tested with the endoscopic factors for the potential variable for the curative resection rate prediction. However, these variables were not consistently identified as important indicators for predicting curative resection [28][29][30]. Although feature importance analysis (Figure 5) or Shapley additive explanations analysis (Multimedia Appendix 6) in our study revealed that age is an important variable for the ML determination process, explainable artificial intelligence analysis is currently an experimental method to understand how ML judges.…”
Section: Discussioncontrasting
confidence: 58%
“…In the context of ecological factors, age and gender have been tested with the endoscopic factors for the potential variable for the curative resection rate prediction. However, these variables were not consistently identified as important indicators for predicting curative resection [28][29][30]. Although feature importance analysis (Figure 5) or Shapley additive explanations analysis (Multimedia Appendix 6) in our study revealed that age is an important variable for the ML determination process, explainable artificial intelligence analysis is currently an experimental method to understand how ML judges.…”
Section: Discussioncontrasting
confidence: 58%
“…Signi cant evidences showed that advanced age, undifferentiated type, tumor size ≥ 2 cm, and presence of ulceration were important factors in causing noncurative ER (28,29). If the elderly did not want to undergo surgery, the above individual characteristics should be evaluated in detail, fully communicated with the patients, and the bene ts and risks should be weighed before nally deciding on the treatment plan.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 systematic review and meta-analysis identified location in the upper third of the stomach (odds ratio (OR) 1.49, 95%CI 1.24–1.79), depressed morphology (OR 1.49, 95%CI 1.04–2.12), and lesions whose identified characteristics lie outside standard criteria (OR 3.56, 95%CI 2.31–5.48) as predictors of this outcome [ 25 ]. Additional risk factors identified in individual studies include large tumor size (generally >20 mm), ulceration, undifferentiated tumors (including the presence of an undifferentiated component in differentiated-type-predominant mixed-type lesions), and old age [ 26 , 27 , 28 , 29 , 30 , 31 ]. Regarding lesion differentiation, a meta-analysis incorporating 5644 patients showed that undifferentiated-predominant mixed-type lesions show more aggressive biological behavior compared to pure undifferentiated-type lesions, presenting a significantly higher risk of submucosal invasion (OR 2.19, 95%CI 1.90–2.52) and LNM (OR 2.28, 95%CI 1.72–3.03) even after stratification for depth of tumor invasion [ 32 ].…”
Section: Indications For Endoscopic Resection: Pre-procedural Evaluationmentioning
confidence: 99%